Complications after surgery for colorectal cancer affect quality of life and surgeon–patient relationship. (December 2014) - Di Cristofaro, L.; Ruffolo, C.; Pinto, E.; Massa, M.; Antoniutti, M.; Cagol, M.; Massani, M.; Alfieri, R.; Costa, A.; Bassi, N.; Castoro, C.; Scarpa, M.
Abstract Aim This multicentric prospective study aimed to investigate how postoperative complications after surgery for colorectal cancer affect patients' quality of life and satisfaction with care. Method One hundred and sixteen patients operated on for colorectal cancer were enrolled in this study. Patients answered three questionnaires about generic (EORTC QLQ‐C30) and disease‐specific (EORTC QLQ‐CR29) quality of life and treatment satisfaction (EORTC IN‐PATSAT32) at the time of admission and at 1 and 6 months after surgery. Non‐parametric tests and linear multiple regression models were used for statistical analysis. Results Twelve patients had complications requiring further surgery (anastomotic leakage, abdominal bleeding, abdominal wall sepsis, wound infection). Patients with complications that required surgery reported a worse score of physical function, emotional function and anxiety than patients without such complications 1 month after surgery. These patients judged their general satisfaction with the quality of care and doctors' interpersonal skills, technical skills, information provision and availability to be worse than in patients without such complications. The presence of postoperative psychiatric complications and anastomotic leakage were independent predictors of quality of life (β = −0.30, P = 0.004, and β = −0.42, P < 0.001). Conclusion In patients undergoing surgery for colorectal cancer, complications requiring any kind of surgical management significantly affected patients' perception of all doctor‐related items suggesting an impairment of the entire surgeon–patient relationship. Convincing patients that 'zero risk' cannot be achieved in surgical practice is therefore a priority.